The Effect of Puzzle Media on Learning Motivation and Mathematics Learning Outcomes in Elementary School Students - Polina Tikara Biantong; Nurdin Arsyad; Suroyo Suroyo (EduLine: Journal of Education and Learning Innovation, 2023)
Media Puzzle is one of the media for learning and playing with demonstration methods will be able to influence student motivation and learning outcomes. In this research, we will analyze the effect of the use of the demonstration method with puzzle media on learning motivation and learning outcomes in mathematics for class IV SDN 1 Rantepao. The following research was carried out using a quantitative approach and was designed using the pre-experimental one group pretest-posttest model. The following research has a population and sample of fourth grade students at SDN 1 Rantepao, a total of 81 students divided into 3 parallel classes. Using the cluster random sampling technique, class IVa was obtained with 27 samples. Data was collected by testing techniques, student activity sheets, questionnaires, and documentation. Based on the test results obtained t count = 20.634> 1.70329, it can be concluded that there is an influence of the demonstration method with puzzle media on learning motivation. Based on the t test on learning outcomes obtained sig. (2-tailed) = 0.000 <0.05, it can be concluded that there is an influence of the demonstration method with puzzle media on learning outcomes..